Effect of Planting Dates on Growth and Yield of Potato (Solanum tuberosum L.) Varieties at Rampur, Chitwan - Gurung, Maya; Giri, Hom Nath (Agronomy Journal of Nepal, 2025)
Potato productivity in Nepal is highly influenced by planting time and varietal adaptability to local agro-climatic conditions. A field experiment was conducted at the Horticulture Farm of Agriculture and Forestry University, Rampur, Chitwan, from September 2021 to February 2022 to evaluate the effect of different planting dates on the growth and yield performance of two potato varieties, Cardinal and MS 42.3. The experiment was laid out in a two-factor factorial randomized complete block design with three replications, comprising four planting dates (September 30, October 15, October 30, and November 15). Growth parameters including emergence, stem number, plant height, leaf number, canopy diameter, and days to physiological maturity, along with yield attributes such as number of tubers per plant, marketable and unmarketable yield, total yield, tuber grading, and dry matter content were recorded and analyzed. Planting date significantly (p < 0.05) influenced most growth and yield parameters, with mid-October planting producing superior vegetative growth and the highest marketable (30.45 mt/ha) and total tuber yield (31.62 Mt ha-1), followed by late October planting, while early and late plantings resulted in comparatively lower performance. Among the varieties, Cardinal produced significantly (p < 0.001) higher marketable (30.14 Mt ha-1) and total yield (31.51 Mt ha-1), whereas MS 42.3 produced more tubers per plant (10.62). The study suggests that planting potato around mid-October using the variety Cardinal is most suitable for achieving higher yield under the agro-climatic conditions of Rampur, Chitwan.